2014
DOI: 10.3390/su6128951
|View full text |Cite
|
Sign up to set email alerts
|

Wind Erosion Induced Soil Degradation in Northern China: Status, Measures and Perspective

Abstract: Soil degradation is one of the most serious ecological problems in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…Our results showed that with increasing vegetation coverage, the amount of soil eroded by wind decreased sharply, and that the higher the wind speed was, the more efficient the protective effect of vegetation on the soil surface was. The relationship between vegetation coverage and wind erosion showed a significant power function correlation (Guo et al, 2014;John et al, 2016). For similar wind regime, the wind erosion rate decreased rapidly with increasing vegetation coverage above a threshold, which is also known as the effective coverage (Leys and Mctainsh, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that with increasing vegetation coverage, the amount of soil eroded by wind decreased sharply, and that the higher the wind speed was, the more efficient the protective effect of vegetation on the soil surface was. The relationship between vegetation coverage and wind erosion showed a significant power function correlation (Guo et al, 2014;John et al, 2016). For similar wind regime, the wind erosion rate decreased rapidly with increasing vegetation coverage above a threshold, which is also known as the effective coverage (Leys and Mctainsh, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Rohrmann et al (2013) also noted that wind had a stronger effect in soil erosion compared with water from the field study of erosion in Qaidam Basin in northern China. Guo et al (2014) pointed out that wind erosion could be the primary factor for soil degradation in arid and semi-arid regions in north China.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate agricultural practices include excessive tillage, use of heavy machinery, excessive and unbalanced use of inorganic fertilizers, poor irrigation and water management techniques, pesticide overuse, inadequate crop residue and/or organic carbon inputs, and poor crop cycle planning. Contributions from both China [24] and Russia [25] focus primarily on wind erosion. To decrease soil loss and enhance local ecosystems, the Chinese government has been encouraging residents to reduce wind-induced soil degradation through a series of national policies and several ecological projects.…”
Section: Geographic Consistency In Soil Degradationmentioning
confidence: 99%